IL‐10 Receptor Neutralization–Induced Colitis in Mice: A Comprehensive Guide. Issue 8 (16th August 2021) - Saha, Piu; Golonka, Rachel M.; Abokor, Ahmed A.; Yeoh, Beng San; Vijay‐Kumar, Matam
Abstract: Interleukin‐10 (IL‐10) and its receptor (IL‐10R) have been foremost targets to understand inflammatory bowel disease (IBD) pathogenesis. For the past several decades, IL‐10‐deficient ( Il10 ‐/‐ ) mice were considered one of the best models to study immune‐mediated colitis. Several physiologic limitations with this model, e.g., delayed and varied disease onset, have hindered investigators in testing new clinical therapies for IBD. In this article, we provide comprehensive guidance for using anti‐IL‐10R monoclonal antibody (αIL‐10R mAb) neutralization as a superior alternative model to study IBD. This article describes the feasibility of using αIL‐10R mAb to induce chronic colitis (within 4 weeks), perform time‐dependent mechanistic studies, and assess the efficacy of IBD therapeutics. This article also delineates protocols for in‐house assays to critically assess colitis and associated inflammatory parameters. Overall, we underscore αIL‐10R mAb neutralization as a relevant immune‐mediated murine colitis model to study human Crohn's disease. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Induction of chronic colitis in mice via αIL‐10R mAb neutralization Basic Protocol 2 : Biochemical evaluation of αIL‐10R mAb neutralization–induced chronic colitis Support Protocol 1 : Stool analysis and scoring Support Protocol 2 : Swiss roll method